The phenomenon of cyberbullying in the children and adolescents population: A scientometric analysis - María-Pilar Cáceres-Reche; Francisco-Javier Hinojo-Lucena; Magdalena Ramos Navas-Parejo; José-María Romero-Rodríguez (Research in Social Sciences and Technology, 2019)
Cyberbullying has become a global problem; cases of violence increase and the rate of suicide by victims has skyrocketed. The purpose of this work was to analyze the scientific production published on cyberbullying in children and adolescents from its beginning until 2018. To this end, a scientific analysis was carried out in the Scopus database, determining diachronic productivity, journals, countries, and institutions with the greatest interest in the subject and articles with greater scientific impact due to the number of citations. In addition, a network map was established to highlight keywords related to cyberbullying in both populations. Among the results, it is worth noting the increase in publications in 2018 and the configuration of certain journals, institutions, countries, and authors as references in the subject. Finally, potential explanations for the findings of the study and suggestions for future research are discussed.